Should lifestyles be a criterion for healthcare rationing? evidence from a portuguese survey - Borges, Ana Pinto (2017)
Background: We evaluated whether different personal responsibilities should influence the allocation healthcare resources and whether attitudes toward the penalization of risk behaviours vary among individual’s sociodemographic characteristics and health related habits. Study design: A cross-sectional study. Methods: We developed an online survey and made it available on various social networks for six months, during 2015. The sample covered the population aged 18 yr and older living in Portugal and we got 296 valid answers. Respondents faced four lifestyle choices: smoking, consumption of alcoholic beverages, unhealthy diet and illegal drug use, and should decide whether each one is relevant when establishing healthcare priorities. Logistic regressions were used to explore the relation of respondents’ sociodemographic characteristics and health related behaviours in the likelihood of agreeing with the patients engaged in risky behaviour deserve a lower priority. Results: Using illegal drugs was the behaviour most penalized (65.5%) followed by heavy drinkers (61.5%) and smoking (51.0%). The slight penalization was the unhealthy dieting (29.7%). The sociodemographic characteristics had different impact in penalization of the risks’ behaviours. Moreover, the respondents who support the idea that unhealthy lifestyles should have a lower priority, all strongly agreed that the smoking habit (OR=36.05; 95% CI: 8.72, 149.12), the unhealthy diets (OR=12.87; 95% CI: 3.21, 51.53), drink alcohol in excess (OR=20.51; 95% CI: 12.09, 85.46) and illegal drug use (OR=73.21; 95% CI: 9.78, 97.83) must have a lower priority in the access to healthcare. Conclusions: The respondents accept the notion of rationing healthcare based on lifestyles.